MATERIALS OF STUDYING PALEOSOLS OF MOUNDS OF THE PALASA-SYRT BURIAL MOUND (GROUP №6) - Idrisov, I A (History, Archeology and Ethnography of the Caucasus, 2015)
The article presents the study group mounds paleosoil No.6 southern part of the Palasa-syrt burial mound of the IV-V centuries. The findings complement those of previous studies, including allowing for greater statistical data to clarify the dynamics of the upland soil during the formation of the burial mound and supports the conclusion of the accelerated evolution of soil at this time, but the reasons for this phenomenon is largely unclear.
Keywords: paleosols; Holocene; Palasa-syrt burial mound; Caucasus